Pengaruh Good Corporate Governance terhadap Nilai Perusahaan Sektor Energy di Indonesi: Menggunakan Carbon Emission Disclosure sebagai Variabel Moderasi - Yuninda Wulan Ayu Gayatri; Vinola Herawaty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The mining industry is a sub-sector that has an important role in contributing to growth in market capitalization. This mining industry can at least contribute to Growth Domestic Product (GDP) of 7.2% or worth 13.8 million. However, the operational activities carried out by a mining industry can be categorized as having a higher potential to damage environmental balance compared to companies in other sectors. Because the activities carried out by this industry include excavation, dredging, and even land clearing which will have the potential to damage an ecosystem. This phenomenon seems to be the focus of attention for business actors in implementing the principles of implementing good corporate governance moderated by carbon emission disclosure in order to increase the value of a company, which in fact is also the aim of this research. The research objects used in this research are companies in the Energy sector listed on the IDX in 2020-2022. The number of samples used in the research was 63 data samples. The results of this research indicate that carbon emission disclosure cannot moderate the influence of managerial ownership and the proportion of independent board of commissioners on firm value. Other results show that managerial ownership and the proportion of independent commissioners greatly influence company value.